2012
DOI: 10.1007/s11292-012-9140-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of military service on criminal offending over the life course: evidence from a Dutch conviction cohort

Abstract: Objectives Examination of the relationship between military service and criminal conviction, and evaluation of its sensitivity through the use of two distinct study designs. Methods Data were collected on the conviction histories of a cohort of men convicted of a crime in 1977 in the Netherlands (n0678). The men were born between 1940 and 1964, and reached the age of military eligibility during an era when service was compulsory, although they could be classified as ineligible or exempt for a variety of reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Moreover, men with extensive prior criminal behavior (i.e., more than six months imprisonment) were deemed ineligible. Also, not all brothers from large nuclear families had to serve [46]: until 1966 the three oldest brothers had to serve, and from that year on only the two oldest brothers were conscripted. Persons who did not undergo medical examination for these or other reasons were excluded from the sample as well.…”
Section: Samplementioning
confidence: 99%
“…Moreover, men with extensive prior criminal behavior (i.e., more than six months imprisonment) were deemed ineligible. Also, not all brothers from large nuclear families had to serve [46]: until 1966 the three oldest brothers had to serve, and from that year on only the two oldest brothers were conscripted. Persons who did not undergo medical examination for these or other reasons were excluded from the sample as well.…”
Section: Samplementioning
confidence: 99%
“…In January 2023, it was announced that some individuals with criminal convictions who had been recruited into the Russian military were set to be pardoned, which may include people with a history of violent felonies (Van Brugen, 2023). Investigations into the correlations between exposure to armed conflict and the increased incidence of post-service violence and criminal behaviours provide mixed evidence for this link (Hjalmarsson & Lindquist, 2019;van Schellen, Apel, & Nieuwbeerta, 2012). Nonetheless, it remains to be seen what implications this could have for recidivism and forensic risk assessments; for those violent offenders with psychiatric morbidities, exposure to a live combat arena in Ukraine, where they lack viable stress reduction mechanisms and sufficient medical care provisions, might invoke serious concerns about their reintegration into the community.…”
Section: People Living In Detentionmentioning
confidence: 99%
“…51 In a Dutch study, Van Schellen, Apel, and Nieuwbeerta found that for a marriage to function as a turning point it is important who you marry, as marriage to a criminal partner could sustain or even stimulate an offender's engagement in criminal activities over time. 52 The study that Sampson and Laub conducted and based their theory on was quantitative, and most researchers who use this life course theory also mainly rely on such data. One of the main critiques on their study came from John Modell.…”
Section: Life Course Criminology: Turning Pointsmentioning
confidence: 99%
“…As mentioned above, marriage to a delinquent person enhances the probability that one continues to commit crimes, and, in the extreme cases, may even intensify one's criminal behaviour. 137 This turning point relies heavily on the impact of social bonds. Not only the social bond with a spouse, but also with the social circle and family of the spouse, since more time will be spent with them as well.…”
Section: Vi3 Marriagementioning
confidence: 99%